Transient diabetes mellitus presenting with diabetic ketoacidosis: a case report - Panuganti, Suresh Kumar; Nukala, Jeevan Reddy; Vempati, Venkateshwar; Modi, Sujeeth Kumar; Patel, Pooja N. (International Journal of Contemporary Pediatrics, 2024)
Neonatal diabetes mellitus (NDM) represents a monogenic form of diabetes mellitus, manifesting with hyperglycemia during the neonatal period. It is relatively a rare condition, affecting an estimated incidence of 1 in every 90,000 live births. Depending on the duration of condition, NDM can be categorized as temporary NDM (TNDM) and permanent NDM (PNDM). We present a case of a 43-day-old infant who presented with diabetic ketoacidosis. Upon evaluation, it was observed that the infant had TNDM, specifically caused by a mutation in the KCNJ11 gene. The infant was initially managed with insulin therapy but was later transitioned to oral sulfonylureas (SU). Initial research suggests that administering SU treatment at an early stage, as opposed to insulin, could enhance neurodevelopmental outcomes in patients who respond well to SU.